Reduced-order filters for neutral systems with distributed delays. (19th May 2017) - Chen, Shaodong; Niu, Ziyu
Abstract: This paper addresses the problem of robust H∞ reduced-order filtering for uncertain neutral systems with distributed delays. A linear matrix inequality H∞ approach is proposed to design a robust H∞ reduced-order filter such that the filtering system remains asymptotically stable and the bound of H∞ norm is less than a given level γ . Moreover, an explicit parameterization of desired robust H∞ reduced-order filter is presented. Two numerical examples are given to illustrate the theoretical results.